Effects of Social Media on Mental Health Among Young Adults of Lahore - Rasheed, Sana; Micheal, Maybal; Jamil, Nayab; Saif, Mutiullah (Biological and Clinical Sciences Research Journal, 2025)
The increasing use of social media among young adults has prompted growing concern over its potential psychological impacts. In the urban context of Lahore, Pakistan, where social connectivity and digital media use are rapidly evolving, understanding this phenomenon is vital. Objectives: To assess the effects of social media use on the mental health of young adults in Lahore, focusing on patterns of use, emotional well-being, and psychological consequences such as sleep disturbance, depression, anxiety, and suicidal ideation. Methods: A descriptive cross-sectional study was conducted over six weeks (April to May 2023) involving 98 young adults aged 18–35 years in Lahore. Participants were selected using non-probability convenience sampling. Data were collected using a pre-tested, self-structured questionnaire covering socio-demographic details and psychological effects of social media. Descriptive analysis was performed using SPSS version 2022. Results: Among participants, 86.7% acknowledged that social media affects mental health, but only 3.1% were aware of its specific impacts. A total of 66.3% reported irritability or sleeplessness due to overuse, while 72.5% believed social media highly impacted their mental health. Alarmingly, 62.2% admitted to frequent suicidal thoughts associated with excessive social media engagement. More than half (52%) reported feelings of depression when comparing their lives to others’ online. Sleep disturbances (73.5%), emotional stress (43.9%), and loneliness (65.3%) were also prevalent. Conclusion: The study highlights a strong association between excessive social media use and adverse mental health outcomes in young adults in Lahore. These include psychological distress, depression, anxiety, suicidal ideation, and disrupted sleep. Interventions promoting responsible social media use, along with educational awareness programs and mental health support, are urgently needed to mitigate these risks.